Carbon content drives high temperature superconductivity in a carbonaceous sulfur hydride below 100 GPa. Issue 65 (15th July 2022) - Smith, G. Alexander; Collings, Ines E.; Snider, Elliot; Smith, Dean; Petitgirard, Sylvain; Smith, Jesse S.; White, Melanie; Jones, Elyse; Ellison, Paul; Lawler, Keith V.; Dias, Ranga P.; Salamat, Ashkan
Abstract : Carbon concentration greatly influences structural and electronic properties of carbonaceous sulfur hydride, almost halving the pressure required for high-TC superconductivity. Abstract : We report a previously unobserved superconducting state of the photosynthesized carbonaceous sulfur hydride (C–S–H) system with a maximum T C of 191(1) K below 100 GPa. The properties of C–S–H are dependent on carbon content, and X-ray diffraction and simulations reveal the system remains molecular-like up to 100 GPa.